A strategic management paper for Massive Trading - Tiu, David Terence Y. (Animo Repository, 2000)
Economic indicators in the Philippines are being by political developments, which are uncertain and unpredictable. Therefore it would be a near impossibility to forecast economic indicators such as exchange, interest and inflation rates. This paper presents a strategic plan in the light of the ever-changing environment in the country. Under present conditions a scenario driven plan will enable organizations to address various uncertainties that beset them. Textile trading belongs to a fragmented industry thus market shares are hard to ascertain. It is also a mature industry that is characterized by: saturation, repeat buying, standardization, less product changes, market segmentation, service emphasis where deals, are prevalent (as evidenced by high relationship marketing). Textile trading regardless of source of good takes on the proverbial quest for profit by an entrepreneur, it functions and fulfills the task of customer service, financing and stocking for an identified product/s. For Massive to be able to continuously enjoy the success thay have, it is important for them to be aware of several strategic issues. First, the company should look into the high dependence on relationship marketing and the possibility of competitive advantage erosion such as the severance of any sales agent which may lead to client loss or better terms and prices from competitors. Second, the fragmented nature of the industry has to be taken into consideration whereby the company must employ certain strategic moves to overcome fragmentation. Third, the economy must look into the number of existing suppliers that they integrate with, and assess whether this number is sufficient and optimal to achieve the company goals and objectives. Lastly, space constraints/congestion in the Divisoria market has resulted in the lease of several warehouses for storage multiple warehouse have brought about problems in inventory monitoring as well as delays in sales tracking and difficulties in purchasing decisions. First, the company depend highly on agents who create relationships with clients and who become sources of feedbacks for competitors' marketing strategies. This atmosphere of relationship marketing has been the most important success factor in the textile, wholesale trading business, but can lead to loss of revenues for the company, if agents decide to leave. This issue can be addressed through an information system/accounting system that will keep a record of all clients where tacit knowledge of the market can be documented, client business volumes can be filed and clients can be tagged, according to credit standing. Second, in addition to the Strategy of Focus and cost leadership, Massive must employ the following strategies in order to overcome fragmentation and improve market share/business activity: Creation of economies of scale and experience curves, specialize by customer type and increase attentive to industry trends. These will be discussed in further details in chapter 5. To address the third issue, Massive should source from suppliers/manufacturers (local or international) that contribute to the firms' competitive advantage. Having focus and cost leadership as their primary strategy, this upstream component of the value chain must be given premium. This will involve the accreditation and the identification of more suppliers that have production technology that essentially brings down the cost for the trader thus providing better margins. The last issue deals with the organizational effectiveness, particularly on monitoring of inventories and tracking of sales, which may also prevent the possibility of losses and increase profitability. Though expenses of Massive are small, it is important for the firm to be able to monitor inventory movement and record sales. This can be done through information technology, acquiring a software that can tag inventories according to location as well as do accounting functions will enable management to arrive at better purchasing decisions. Massive's position as a wholesaler in the textile trading industry has a great potential. Internally, they must continue to source goods at better prices to be able to fulfill wholesaler competencies and responsibilities of bulk-breaking and thus deliver and provide better price advantage. Update the current technology will also have a great impact on the cost reductions and better purchasing and management decisions. And employ specific strategies for fragmented industries to further improve the business. External factors on the domestic and international fronts such as trade liberalization and the growth of the garments market and industry should also be fully utilized by the company. Together, these factors open a future for Massive that is both viable and profitable at a sustainable level.